Reactive superhydrophobic surface and its photoinduced disulfide-ene and thiol-ene (bio)functionalization - Li, Junsheng; Li, Linxian; Du, Xin; Feng, Wenqian; Welle, Alexander; Trapp, Oliver; Grunze, Michael; Hirtz, Michael; Levkin, Pavel (Nano letters, 2015)
Reactive superhydrophobic surfaces are highly promising for biotechnological, analytical, sensor, or diagnostic applications but are difficult to realize due to their chemical inertness. In this communication, we report on a photoactive, inscribable, nonwettable, and transparent surface (PAINTS), prepared by polycondensation of trichlorovinylsilane to form thin transparent reactive porous nanofilament on a solid substrate. The PAINTS shows superhydrophobicity and can be conveniently functionalized with the photoclick thiol-ene reaction. In addition, we show for the first time that the PAINTS bearing vinyl groups can be easily modified with disulfides under UV irradiation. The effect of superhydrophobicity of PAINTS on the formation of high-resolution surface patterns has been investigated. The developed reactive superhydrophobic coating can find applications for surface biofunctionalization using abundant thiol or disulfide bearing biomolecules, such as peptides, proteins, or antibodies.
Published: December 8, 2014
Gesehen am 18.06.2020